2016
DOI: 10.1175/jas-d-15-0245.1
|View full text |Cite
|
Sign up to set email alerts
|

An Ensemble Approach to Investigate Tropical Cyclone Intensification in Sheared Environments. Part II: Ophelia (2011)

Abstract: The mechanisms leading to tropical cyclone (TC) intensification amid moderate vertical wind shear can vary from case to case, depending on the vortex structure and the large-scale conditions. To search for similarities between cases, this second part investigates the rapid intensification of Hurricane Ophelia (2011) in an environment characterized by 200-850-hPa westerly shear exceeding 8 m s 21 . Similar to Part I, a 96-member ensemble was employed to compare a subset of members that predicted Ophelia would i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 40 publications
2
20
0
Order By: Relevance
“…Earlier studies have used the criteria of 200-hPa EFC . 10 m s 21 day 21 from 300-to 600-km radius to indicate TC-trough interaction (DeMaria et al 1993;Hanley et al 2001;Rios-Berrios et al 2016). In this simulation, this criterion is met in the 300-100-hPa layer (or the 200-hPa level, not shown) at 120 h. In theory, if EFC is directly affecting the outflow, a maximum in y r should appear around this time frame at larger radii and propagate radially inward with time.…”
Section: Eddy Fluxesmentioning
confidence: 84%
See 1 more Smart Citation
“…Earlier studies have used the criteria of 200-hPa EFC . 10 m s 21 day 21 from 300-to 600-km radius to indicate TC-trough interaction (DeMaria et al 1993;Hanley et al 2001;Rios-Berrios et al 2016). In this simulation, this criterion is met in the 300-100-hPa layer (or the 200-hPa level, not shown) at 120 h. In theory, if EFC is directly affecting the outflow, a maximum in y r should appear around this time frame at larger radii and propagate radially inward with time.…”
Section: Eddy Fluxesmentioning
confidence: 84%
“…A number of studies have examined the interaction of a TC and a trough for real cases using reanalyses, model analyses, or real-data simulations (e.g., Riehl 1954;Sadler 1976Sadler , 1978Holland and Merrill 1984;Vollaro 1989, 1990;Hanley et al 2001;Yu and Kwon 2005;Barrett et al 2016;Rios-Berrios et al 2016). Comparatively few studies exist in the literature that examine TC-trough interaction in a more fundamental manner such as in a modeling framework (Shi et al 1990;Kimball and Evans 2002;Ge et al 2008;Rappin et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Despite these limitations, our simulations confirm several studies that document compromised TC predictability in environments with moderate vertical wind shear (Bhatia & Nolan, ; Rios‐Berrios et al, ). We have further demonstrated that the predictability of TC intensity and the low‐wave‐number precipitation structure depends on the vertical distribution of moderate shear.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Such shear magnitudes are near the threshold values that are commonly used to differentiate favorable from unfavorable flow environments (e.g., Gallina & Velden, ; Paterson et al, ). Not surprisingly, the limited predictability of numerous TC cases has been at least partially attributed to the presence of vertical wind shear within this moderate range (Munsell et al, ; Rios‐Berrios et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…A major impediment of accurate tropical cyclone (TC) forecasts is the interaction of TCs with environmental vertical wind shear (VWS). Although VWS is one of the most inhibiting factors of TC intensification (Merrill 1988;DeMaria and Kaplan 1994;Paterson et al 2005;Hendricks et al 2010), TCs can intensify under VWS magnitudes that are neither too weak nor too strong (moderate shear hereafter; Molinari et al 2004Molinari et al , 2006Molinari and Vollaro 2010;Montgomery et al 2010;Foerster et al 2014;Stevenson et al 2014;Rios-Berrios et al 2016b,a;Zawislak et al 2016;Rios-Berrios and Torn 2017;Nguyen et al 2017). Consequently, intensity changes are more difficult to predict for moderate VWS scenarios than for weak or strong VWS (Bhatia and Nolan 2013;Finocchio and Majumdar 2017).…”
Section: Introductionmentioning
confidence: 99%